Correction: Evaluation of circulating microRNA profiles in Brazilian women with polycystic ovary syndrome: A preliminary study. - Giovana De Nardo Maffazioli; Edmund Chada Baracat; José Maria Soares; Kátia Cândido Carvalho; Gustavo Arantes Rosa Maciel (PLoS ONE)
[This corrects the article DOI: 10.1371/journal.pone.0275031.].